2012
DOI: 10.1515/hf-2012-0011
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DCM extractable components from hot-pressed hybrid poplar

Abstract: The effects of thermal compression on the organic-soluble material of a uniform wood substrate, hybrid poplar (clone OP-367), has been studied. Poplar veneers were preconditioned to 0% or 8% moisture content and subsequently hot pressed at 150°C, 200°C, and 250°C. The dichloromethane (DCM) extracts were characterized by various hyphenated analyses [gas chromatography-mass spectrometry (GC-MS), analytical pyrolysis (Py-GC-MS), electrospray ionization-mass spectrometry (ESI-MS), and gel permeation chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…Molar mass of the lignin and D1 prepolymer samples were determined by positive ion ESI‐MS on a LCQ‐Deca instrument (Thermo Quest). Samples were dissolved in methanol (1 mg mL −1 ) containing 1% acetic acid and introduced into the ESI source at a flow rate of 10 μL min −1 . The ion source and capillary voltages were 4.48 kV and 47 V, respectively, at a temperature of 275°C.…”
Section: Methodsmentioning
confidence: 99%
“…Molar mass of the lignin and D1 prepolymer samples were determined by positive ion ESI‐MS on a LCQ‐Deca instrument (Thermo Quest). Samples were dissolved in methanol (1 mg mL −1 ) containing 1% acetic acid and introduced into the ESI source at a flow rate of 10 μL min −1 . The ion source and capillary voltages were 4.48 kV and 47 V, respectively, at a temperature of 275°C.…”
Section: Methodsmentioning
confidence: 99%
“…The lipids from the RBB were extracted with CH 2 Cl 2 and quantified according to the method of Osman et al [25]. Carbohydrate content of lipid-free RBB after CH 2 Cl 2 extraction was analyzed as previously described [26,27].…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Cellulose crystallinity was determined using both the relative band heights of 1,429/897 cm −1 (Akerholm et al 2004) and relative band areas of 1,375/ 2,900 cm −1 (Nelson and O'Connor 1964a, b). For molecular weight analysis of cellulose, extractive-free wood (Osman et al 2012) was first delignified using NaClO 2 to form holocellulose (Wise et al 1946). The holocellulose samples (20 mg) were derivatized to their tricarbanilate form on reaction with phenylisocyanate in pyridine at 80°C for 48 h and isolated after precipitation with 30 % aqueous methanol (Suckling et al 2001).…”
Section: Cellulose Analysismentioning
confidence: 99%
“…Thermal treatment affects lignin and cellulose as well. Osman et al (2012Osman et al ( , 2013 observed an increase in the dichloromethane extractive content (9 %) in hot-pressed poplar around 250°C, which mainly comprised solubilized lignin. Reduction of lignin molecular weight was induced by lignin depolymerization.…”
Section: Introductionmentioning
confidence: 99%